2017
DOI: 10.1021/acs.inorgchem.7b02516
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Construction of Heterobimetallic Cages by an Extended Molecular Library Approach

Abstract: Two novel heterobimetallic complexes, a trigonal-bipyramidal and a cubic one, have been synthesized and characterized using the same C-symmetric metalloligand, prepared by a simple subcomponent self-assembly strategy. Adopting the molecular library approach, we chose a mononuclear, preorganized iron(II) complex as the metalloligand capable of self-assembly into a trigonal-bipyramidal or a cubic aggregate upon coordination to cis-protected C-symmetric palladium(II) or unprotected tetravalent palladium(II) ions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 72 publications
1
39
0
5
Order By: Relevance
“…In conclusion, we presented the stepwise assembly of two heterobimetallic cages BP‐1 and CU‐1 from the same C 3 ‐symmetric metalloligand ML‐1 adopting the well‐implemented molecular library approach. Compared to previously reported diamagnetic complexes ML‐2 , BP‐2 , and CU‐2 the simple addition of a methyl group in 6‐position of the pyridyl ring leads to a substantial amount of steric strain and changes the spin state of the iron(II) cations from diamagnetic low spin to paramagnetic high spin. This impressively shows how rather small changes of the ligand system can cause tremendous changes of the complex properties.…”
Section: Methodsmentioning
confidence: 64%
See 2 more Smart Citations
“…In conclusion, we presented the stepwise assembly of two heterobimetallic cages BP‐1 and CU‐1 from the same C 3 ‐symmetric metalloligand ML‐1 adopting the well‐implemented molecular library approach. Compared to previously reported diamagnetic complexes ML‐2 , BP‐2 , and CU‐2 the simple addition of a methyl group in 6‐position of the pyridyl ring leads to a substantial amount of steric strain and changes the spin state of the iron(II) cations from diamagnetic low spin to paramagnetic high spin. This impressively shows how rather small changes of the ligand system can cause tremendous changes of the complex properties.…”
Section: Methodsmentioning
confidence: 64%
“…Thus, it is possible to transfer all advantages of the subcomponent self‐assembly approach to systems consisting of more than one type of metal cation. However, to date only a few examples of heterobimetallic complexes have been reported that were built up from subcomponents …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ar adically different outcomeiso bserved in the coordination of 1 to CuPF 6 ,c ontaining aw eakly-coordinating anion. The 1:1 reaction of 1 with [Cu(NCMe) 4 ]PF 6 gives the complex [Cu(1)(NCMe)] 4 [PF 6 ] 4 in 91 %i solated yield ( Figure 4) (see Exper-imentalS ection). The X-ray crystal structure showsacage arrangementi nw hich four of the ligands 1 bridge the four Cu centres,u sing all three pyridyl arms, into ad iscrete [{Cu(1)(NC-Me)} 4 (&PF 6 )] 3 + cation.…”
Section: Resultsmentioning
confidence: 99%
“…[2] Severin and co-workersh ave overcome this tendency by incorporatinga dditional steric groups into bis(3-pyridyl) Fe clathrochelate ligandst op roduce Pd 6 L 12 12 + cages, [2] and have found that tuningt he sterics alters the size of the cage. [3] This metalloligand strategy for the construction of heterometallic supramolecular architectures has been successfully enacted for av ariety of mixed transition metals ystems, for example, Fe/Pd, [2,[4][5][6] Fe/Ru, [7] Fe/Co, [8,9] Co/ Mn [5] and Ru/Pd. [10,11] However,t he use of main group metalloligands to createmixed main group/transitionmetal heterometallic systems is rare.…”
Section: Introductionmentioning
confidence: 99%